Impact of DPYD, DPYS, and UPB1 gene variations on severe drug‐related toxicity in patients with cancer. Issue 9 (20th July 2020) - Yokoi, Katsuyuki; Nakajima, Yoko; Matsuoka, Hiroshi; Shinkai, Yasuko; Ishihara, Takuma; Maeda, Yasuhiro; Kato, Takema; Katsuno, Hidetoshi; Masumori, Koji; Kawada, Kenji; Yoshikawa, Tetsushi; Ito, Tetsuya; et al.
Abstract: Cancer treatment with a fluoropyrimidine (FP) is often accompanied by severe toxicity that may be dependent on the activity of catalytic enzymes encoded by the DPYD, DPYS, and UPB1 genes. Genotype‐guided dose individualization of FP therapy has been proposed in western countries, but our knowledge of the relevant genetic variants in East Asian populations is presently limited. To investigate the association between these genetic variations and FP‐related high toxicity in a Japanese population, we obtained blood samples from 301 patients who received this chemotherapy and sequenced the coding exons and flanking intron regions of their DPYD, DPYS, and UPB1 genes. In total, 24 single nucleotide variants (15 in DPYD, 7 in DPYS and 2 in UPB1 ) were identified including 3 novel variants in DPYD and 1 novel variant in DPYS . We did not find a significant association between FP‐related high toxicity and each of these individual variants, although a certain trend toward significance was observed for p.Arg181Trp and p.Gln334Arg in DPYS ( P = .0813 and .087). When we focused on 7 DPYD rare variants (p.Ser199Asn, p.IIe245Phe, p.Thr305Lys, p.Glu386Ter, p.Ser556Arg, p.Ala571Asp, p.Trp621Cys) which have an allele frequency of less than 0.01% in the Japanese population and are predicted to be loss‐of‐function mutations by in silico analysis, the group of patients who were heterozygous carriers of at least one these rare variants showed a strong association with FP‐related high toxicity ( P = .003). Although the availability of screening of these rare loss‐of‐function variants is still unknown, our data provide useful information that may help to alleviate FP‐related toxicity in Japanese patients with cancer. Abstract : This is the first report to assess the clinical relevance of DPYD, DPYS, and UPB1 variants as predictors of severe FP‐associated toxicity in East Asians. This study shows rare DPYD variants which cause a loss‐of‐function in silico and a DPYS p.Gly334Arg polymorphism may be associated with severe FP‐related toxicity in Japanese patients with cancer. However, the common UPB1 pathogenic variant p.Arg326Gln in the Japanese population does not show a clear association with toxicity in heterozygous individuals.